Sistem Informasi Penjualan Berbasis Kinerja pada Proyek Apartemen Mega City Bekasi - Dyani Ayu Aisyah; Kursehi Falgenti (Jurnal Nasional Teknologi dan Sistem Informasi, 2017)
Mega City Apartment Bekasi is an integrated residence with shopping and office center developed by PT. Mega Utama Development. The sales data encountered in the Mega City apartment project is still manualy by using speadsheet application. There has been no centralized data processing with an application support, especially marketing division. The purpose of this study to build a performance-based sales information system at PT. Mega Utama Development. The method used in developing this information system is SDLC. The SDLC model used in the development of this information system is the "Classic Life Cycle" or waterfall model. With the support of performance-based sales information system, the sales process of apartment units in PT. Mega Utama Development becomes more effective and marketing managers can directly control the performance of sales eksekutifs based on performance reports on this information system.